Ty jestes jak zdrowie : z Mickiewiczem nad Wilia i Switezia, ze Slowackim w Krzemiencu, z Orzeszkowa nad Niemnem - Wachowicz, Barbara (Warszawa : Oficyna Wydawnicza Rytm, 1994)
A travelogue of the regions and homes of three noted Polish literary figures: Mickiewicz, Slowacki, and Orzeszkowa.
Keywords: Mickiewicz, Adam, -- 1798-1855 -- Homes and haunts -- Lithuania; Slowacki, Juliusz, -- 1809-1849 -- Homes and haunts -- Ukraine -- Kremenets; Orzeszkowa, Eliza, -- 1842-1910 -- Homes and haunts -- Lithuania; Authors, Polish -- 19th century -- Biography; Lithuania -- Description and travel; Kremenets (Ukraine) -- Description and travel